Reconstruction of the Interpretive Level in the Structure of a Linguistic Personality as a Participant of Virtual Dialogic Communication - Nadezhda N. Shpilnaya; Elena N. Skubieva (Виртуальная коммуникация и социальные сети, 2022)
The authors reconstructed the interpretive level in the model of a linguistic personality as a participant in a virtual dialogue. The authors proceeded from the understanding that the model of a linguistic personality includes the following levels: 1) superficial understanding of the speech product to create a response text, 2) interpretation, 3) modus level, 4) intertextual level. The interpretational level includes interpretation of the perceived initial cue. Interpretation in this case is a mental-linguistic activity, during which the meaning of the original message is appropriated by its addressee and verbalized in the response message. The following interpretative strategies serve here as description units: author- and text-oriented, holistic and elementary, linguistic trust and linguistic skepticism, copyial and creative. The research featured responses of native speakers published on the portal of the Bankfax news agency. The analysis of dialogic utterances was followed by a reconstruction of the interpretive level in the structure of a linguistic personality as a participant in virtual dialogue. The author of the response proved to be an active interpreter with various interpretation strategies.